Aspectos clínicos e nutricionais de crianças com cardiopatias congênitas internadas em um hospital de referência em Belém, Pará. - GALLON, Mikaela (2023)
The present study aims to describe the clinical and nutritional aspects of children diagnosed with congenital cyanotic and acyanotic heart disease. Descriptive and analytical crosssectional study carried out at the Hospital de Clínicas Gaspar Viana Foundation from May 2019 to February 2020. Children, between 5 and 10 years old, diagnosed with congenital heart disease, were evaluated, of whom the guardians agreed to sign the Informed Consent Form. Socio economic data, clinical data, biochemical tests, functional capacity, anthropometry and semiological analysis were analyzed. The data were tabulated in the Excel® 2010 program and analyzed statistically using the Statistical Package for Social Science software, version 21. 33 children with an average age of 7 years and 7 months ± 1.7 were evaluated, with no statistical significant difference between genders . Acyanotic heart disease was the most recurrent (54.55%), however Tetralogy of Fallot was the most common diagnosis (21.21%). Regarding functional capacity, 57.58% were restricted to strenuous activities while normal levels were found in most parameters: hemoglobin (63.64%; n = 21; p = 0.001), hematocrit (60.61%; n = 20; p = 0.004), creatinine (81.82%; n = 27; p = <0.000), body mass index / age (72.73%; n = 24; p = <0.000), nails (51.52%; n = 17; p = <0.000), lips (75.76%; n = 25; p = <0.000) and skin (69.70%; n = 23; p = <0.000). It is concluded that the presence of a nutritionist from the multiprofessional team is essential in order to assess possible nutritional deficiencies that interfere with the treatment.